Progress in Studying the Impact of Exercise on Obesity in Children and Adolescents - Liu Song (International Journal of Education and Humanities, 2024)
At present, obesity in children and adolescents is popular, and the current situation of obese children and adolescents is not optimistic. This paper discusses the influence of obesity on children and adolescents, and sorts out the existing research results on the effect of exercise intervention on obese children and adolescents, clarifies the important role of exercise intervention to improve obese children, and believes that the future research on exercise intervention to improve obese children and adolescents should explore the effectiveness and safety of intervention. In this paper, through the CNKI, wan fang database database, select nearly three years 31 representative articles related to the influence of sports on obese adolescents, from the present situation of children and adolescents obesity, influencing factors, solutions, the future outlook four dimensions for a comprehensive comb, points out the shortcomings